Gestão escolar itinerante: novos tempos... novos desafios... - Bertolani, Iara Cabral de Athayde (2025)
The general objective of this research was to investigate the limits and responsibilities of pedagogical management from an itinerant perspective. The research provides a timeline of school management in Brazil from the Jesuits to the present, pointing out the challenges of management in contemporary times. Itinerant management, a concept that allows a broad view of the educational system, is complex and presents itself in different dimensions. The watchword of itinerant management is mediation, an important term that makes it possible to weave networks so that the work of the school team is engaged and organized. Being an itinerant manager means understanding that there are challenges and complexities in the role, that respect for local specificities is essential and that working in continuous partnership is a basic premise for fluid relationships. The methodological path taken to organize this dissertation was qualitative, interpretative and descriptive research. The bibliographical survey and documentary analysis were essential in the preparation of this dissertation, as they provided essential data that supported the research. The theoretical subsidies for our analysis of the concept of management were texts by authors such as Vitor Paro, Heloisa Lück and José Carlos Libâneo, among others